Computer use and active learning behaviors of secondary school students - Austria, Marilyn C. (2007)
The use of advanced technology is important in making any country globally competitive. The study was conducted to find out the active learning behaviors of the students when they use and do not use computers with the following: word processors, presentation and authoring software, CD-ROM materials for learning, and the Internet; and the relationship of the active learning behaviors with the following factors: gender, level of education, age, amount of time and length of years using computers, and the availability of computers. A survey was done in Ecumenical Christian College. Descriptive analysis utilizing inferential statistics and weighted mean interpretations were applied in analyzing the data. The study revealed that computer use had considerable influence towards active learning. Therefore, it is important that school administrators, teachers, parents, and students be able to appropriately use computers to achieve active learning.